Financial Sector Assessment : Barbados - World Bank (Washington, DC, 2013)
As part of the joint International Monetary Fund (IMF)-World Bank Financial Sector Assessment Program (FSAP), a mission visited Barbados during June 24 to July 12, 2002. The principal objective of the mission was to assist the authorities in identifying potential vulnerabilities in the financial system that could have macroeconomic consequences and to identify measures to reduce these risks. The mission also provided an assessment of the observance of international standards and codes in financial regulation and supervision as well as of the development needs of the financial system and its potential contribution to economic development. Preliminary results of the mission were discussed with the authorities during the International Monetary Fund (IMF) article four missions in October 2002.